KERJA SAMA BILATERAL INDONESIA DAN HONG KONG SPECIAL ADMINISTRATIVE REGION MENGENAI STOLEN ASSET RECOVERY : STUDI KASUS BANK CENTURY - Samudra Ginting; Ika Riswanti Putranti; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research aims to explain the obstacles to implementation of Century Bank's asset recovery in the Hong Kong jurisdiction. Asset recovery efforts from Hong Kong Jurisdiction has been undertaken by the Government of Indonesia through bilateral agreements on Mutual Legal Assistance in Criminal Matters. However, the efforts have some obstacles from 2009 to 2016 , so that the asset has not been returned successfully. This research uses compliance theory with rationalism approach from realist tradition. Then the method used in this researh is qualitative, with the kind of exploratory research through interview data collection techniques and literature. The result of this researh is Hong Kong has not complied to the content of agreement. This non-compliance is related to the rational act of Hong Kong government. In addition, the rational choice of Hong Kong is keeping the principle of financial confidential.